Iodine‐Transfer Polymerization (ITP) of Ethylene and Copolymerization with Vinyl Acetate. Issue 43 (24th August 2020) - Wolpers, A.; Baffie, F.; Verrieux, L.; Perrin, L.; Monteil, V.; D'Agosto, F.
Abstract: Controlled radical polymerization of ethylene using different commercially available, cheap, and non‐toxic iodo alkyls is performed by iodine transfer polymerization (ITP) under mild conditions (≤100 °C and ≤200 bar). The formed well‐defined iodo end‐capped polyethylene (PE−I) species is very stable upon storage. Narrow molar‐mass distributions (dispersities around 1.6) were obtained up to number average molar masses of 7300 g mol −1 . The ethylene copolymerization by ITP (ITcoP) with vinyl acetate allowed to form a broad range of poly(ethylene‐ co ‐vinyl acetate) (EVA) containing from 0 to 85 mol % of VAc unit. In addition, EVA‐ b ‐PE block copolymers or EVA‐ b ‐EVA gradient block copolymers with different content of VAc in the blocks were obtained for the first time using ITP. Finally, reactivity trends were explored by a theoretical mechanistic study. This highly versatile synthetic platform provides a straightforward access to a diverse range of well‐defined PE based polymer materials. Abstract : Controlled radical polymerization of ethylene was conducted through ITP. Copolymerization with vinyl acetate provides a range of well‐defined structures, including poly(ethylene‐ co ‐vinyl acetate) containing VAc from 0 to 85 mol %.